2020
DOI: 10.1177/0300060520904847
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34c-3p target inhibiting NOTCH1 suppresses chemosensitivity and metastasis of non-small cell lung cancer

Abstract: Background Chemotherapy is the standard treatment for non-small cell lung cancer (NSCLC). However, chemoresistance frequently occurs, making the treatment of NSCLC more difficult. Method We combined clinical and experimental studies to establish the role of microRNA (miR)-34c in NSCLC metastasis and chemoresistance. Results MiR-34c expression was significantly decreased in patients with NSCLC who showed a poor chemoresponse and metastasis. Overexpression of miR-34c sensitized NSCLC cells to paclitaxel and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Notch1 translocation enhances the expression of downstream target oncogenes including cyclin D1 and homeobox protein NANOG (28,29). Notch1 has been revealed to be highly expressed as an oncogene in various cancers including non-small cell lung, breast, liver and gastric cancer (30)(31)(32)(33). The present study confirmed that miR-34c-5p impaired Notch1 expression by directly binding to the 3'-UTR of Notch1 mRNA.…”
Section: Discussionsupporting
confidence: 82%
“…Notch1 translocation enhances the expression of downstream target oncogenes including cyclin D1 and homeobox protein NANOG (28,29). Notch1 has been revealed to be highly expressed as an oncogene in various cancers including non-small cell lung, breast, liver and gastric cancer (30)(31)(32)(33). The present study confirmed that miR-34c-5p impaired Notch1 expression by directly binding to the 3'-UTR of Notch1 mRNA.…”
Section: Discussionsupporting
confidence: 82%
“…miR-21 PTEN [55][56][57][58] miR-27a RKIP [59,60] miR-92b-3p PTEN [23,61] miR-130b PTEN [62] miR-146a CHOP [54] miR-224 p-21 [62] miR-324-5p FBXO11 [63] miR-425-3p AKT1 [26] miR-1269b PTEN [64] let7 a,b,c,d,e,f,g,i LIN28 [36,48] miR-29c AKT2 [65] miR-30b-5p LRP8 [66] miR-34c-3p Notch [35] miR-100-5p mTOR [25] miR-101 ABCC1, ROCK2 [67,68] miR-145-5p ABCC1 [69] miR-146a JNK2, CEACAM6, CCNJ [70][71][72] miR-181b BCL2, TGFβR1, Notch2 [73][74][75][76] miR-193 LRRC1 [77] miR-378 sCLU [78] miR-379 EIF4G2 [79] miR-381 NFkB [80] miR-451a MCL-1 [81][82][83] miR-486-5p TWF1 [84] miR-613 GJA1 [85,86] DDP-cisplatin; DDP-S miRNA-miRNA associated with DDP sensitivity; DDP-R miRNA-miRNA associated with DDP resistance.…”
Section: Ddp R/ddp S Mirna Downstream Regulation Referencementioning
confidence: 99%
“…Cai et al found that miR-128-3p upregulation increased resistance to multiple drugs though used alone (cisplatin, gemcitabine, or paclitaxel; [ 62 ]), probably suggesting a similar effect when combined therapy would be otherwise used. Other miRNAs were also identified to regulate sensitivity to both cisplatin and paclitaxel (i.e., miR-186-5p [ 63 , 64 ]; miR-17-5p [ 22 , 65 , 66 ]; miR-34c-3p [ 67 ]) or cisplatin and docetaxel (miR-141-3p [ 68 , 69 ]; and miR-379-5p [ 70 , 71 ]).…”
Section: Relevant Sectionsmentioning
confidence: 99%